2017
DOI: 10.15390/eb.2017.6447
|View full text |Cite
|
Sign up to set email alerts
|

Student Absenteeism in Secondary Education, Absenteeism-Related School Practices and Recommended Policies

Abstract: Bu araştırma, ortaöğretimde öğrenci devamsızlığını, buna dönük okul uygulamalarını ve bu sorunun azaltılmasına yönelik önerilen politikaları saptamak amacıyla yapılmıştır. Araştırma, hem nicel hem de nitel araştırma yaklaşımına göre tasarlanmış karma bir çalışmadır. Araştırmada, 625 öğrenci ile 6 yönetici ve 5 rehber öğretmenden veri toplanmıştır. Araştırmanın verileri Özbaş (2010) tarafından geliştirilen "Devamsızlık Nedenleri Görüşme Ölçeği" ile yarı yapılandırılmış görüşme formu aracılığıyla elde edilmiştir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…It would be beneficial to initiate lines of research in this area. These results are also consistent with researches that highlighted the relationship between maltreatment against students and absenteeism [9,15].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…It would be beneficial to initiate lines of research in this area. These results are also consistent with researches that highlighted the relationship between maltreatment against students and absenteeism [9,15].…”
supporting
confidence: 92%
“…In the academic community, absenteeism has been reported as a key risk factor for violence, injury, substance use, food insecurity, psychiatric disorders, and economic deprivation [8][9][10][11]. For this reason, educational researchers have focused on the factors that cause absenteeism, which have been studied in various contexts and at various educational levels [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the reasons for the problem of absenteeism at various levels of education were exposed based on the opinions of stakeholders such as students, teachers, administrators, and inspectors. There are also studies evaluating the effectiveness of practices to reduce absenteeism along with the causes of absenteeism (Onder, 2017;Pehlivan, 2006). Research examining the effects of absenteeism on school management and the educational environment and processes is limited.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Another study by Önder [8] showed that the biggest reason for irregular attendance is due to students' individual psychological problems or the groups around them. The common view reached at the end of this study stressed the need for a widespread professional support to minimize or put an end to irregular attendance problem.…”
Section: Risk Management Strategies and Policiesmentioning
confidence: 99%